Fabrication and characterization of metal nanostructures and graphene nanolayers and their application in optical sensing / Mezher H Mezher - Mezher , H Mezher (2018)
We present a study of optical characteristics of metal and graphene oxide nano-layers and their application in optical sensing. The nano-layers are coated using different approaches such as electron beam evaporation, electrochemical deposition and drop casting technique. Gold and silver nanoparticle layers were fabricated using electron beam evaporation followed by subsequent thermal annealing at different temperature and duration to achieve de-wetting of the metal thin film. Morphological analysis was carried out to study the shape and size of the produced nanoparticles. The gold and silver nanoparticles have sizes ranging from 11 nm to 45 nm and 15 nm to 54 nm, respectively. Meanwhile, bilayer Au/Ag-NPs have also been fabricated with particle size in the range between 23nm and 26 nm. On the other hand, the effects of nanostructures were studied using silver micro-flowers (Ag-MFs) with sizes of ~150-500 nm and platinum ‗dome-like‘ nanostructures (Pt-NSs). Absorption spectroscopy was carried out to study the Surface Plasmon Resonance (SPR) of the nanoparticle layers. The shape and size of the nanoparticles are observed to affect the shifting of SPR wavelengths. Nonlinear optical properties was obtained for different structures of nano-layers using Z-scan technique. The nonlinear refractive index and nonlinear absorption coefficient of the nano-layers were determined. The Au-NPs show increase in the NLA and NLR with the increase in nanoparticle size. Meanwhile, The Au/Ag-NPs exhibit NLA and NLR between Au-NPs and Ag-NPs. The nonlinear optical properties of Ag-MFs with increase the size of microflower show increase in the NLA and NLR. Due to thermal effect, nonlinear absorption and nonlinear refraction index are not constant values and depend on the incident intensity. Increases the intensity that apply on Pt-NSs show reduce NLA and NLR value and also for nitrogen doped graphene show reduce in NLA and NLR when increase the incident intensity. From the state of increasing the incident intensity can decreasing in the NLR due to thermal nonlinearity. The GO show increase in NLA and NLR with the increase in thickness. Selected nano layers (Platinum and Graphene oxide) are applied on optical waveguides for detection the water content in transformer oil. Pt-NPs coated planar waveguide sensor shows the sensitivity to dissolved water in transformer oil of -0.561 dB/ppm, while Pt-NPs coated D-Fiber sensor shows a sensitivity of -0.88 dB/ppm. GO have been coated on planar waveguide and D-Fiber to measure the water content in transformer oil. Depending on the GO coating thickness, the sensitivity range from 0.3 dB/ppm of water content in transformer oil to 1.86 dB/ppm of water content in transformer oil. The stability of the sensor output is inversely proportionate to the sensitivity, meaning there is a compromise between the two parameters when considering devising optical sensors in this configuration. The GO-coated waveguide sensor is further tested with continuous varying water content in transformer oil using a fluidic channel structure, and the result shows that the sensor is able to discern changes in water content in transformer oil in simulated environment.